THE IMPACT OF METACOGNITIVE STRATEGIES ON STUDENTS’ MOTIVATION IN READING COMPREHENSION - Riany, Yulina Eva (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
Education, which is believed as a fundamental role to play in developing of human resources, is directly affected by the school system and the learning methods. Implementing metacognitive strategies in learning methods are expected to have positive association with the developing of students’ learning methods, particularly in reading methods. However, although implementing metacognitive strategies in reading comprehension is believed to have positive association with students’ reading performance and motivation, it seems rarely to be applied in the reading comprehension strategies. The purpose of this study was to study the effectiveness of teaching and implementing one of metacognitive strategies, which was generating questions before, during, and after reading on student’s motivation and reading performance. This study was looking at how metacognitive strategies could be implemented in reading strategies and how they could change student’s motivation, including student’s self efficacy, interest, and attribution. Teaching metacognitive strategies were conducted three times to an international university student and the observation was done by using think aloud method and filling a motivational questionnaire. Motivation (self-efficacy, interest, and attribution) changes have revealed after the metacognitive training given. However, there is no difference in reading comprehension performance before and after implementing the metacognitive strategies. It was found that motivation changes did not associate with reading comprehension performance in this study. More comprehensive and explicit metacognitive training in longer time was suggested to see the improvements of the reading comprehension.